DAMPAK APLIKASI INSEKTISIDA BERBAHAN AKTIF EMAMEKTIN BENZOAT DAN DELTAMETRIN TERHADAP MORTALITAS DAN KEMUNCULAN IMAGO Trichogramma japonicum DI LABORATORIUM - Hanif Maulana Ahmad; Noni Ramadhini; Hery Nirwanto (The University of Lampung, 2026)
The use of chemical insecticides remains the primary solution to agricultural pest problems. The use of insecticides does not entirely solve the problem, but can disrupt the existence of non-target organisms (parasitoids). This research aims to determine the effects of the active ingredients emamectin benzoate and deltamethrin on the mortality, morphological behavioral changes, and the emergence rate of T. japonicum imagoes. Testing was conducted using fresh residual and fresh residual contact methods. The process of rearing T. japonicum imagoes included breeding the host C. cephalonica, preparing the substrate, and rearing T. japonicum. Fresh residual and fresh residual contact tests were conducted using field concentrations of 2 ml/L and 3 ml/L, respectively for active ingredients emamectin benzoate and deltamethrin. Observation parameters included mortality rates, morphological changes, behavioral changes, and the emergence rate of T. japonicum imagoes. Mortality data were analyzed using a normality test. If the data were not normally distributed, the Kruskal-Wallis test (non-parametric) and Mann-Whitney test were employed, along with probit analysis of the lethal time 50 (LT50). The research results showed that the active ingredients emamectin benzoate and deltamethrin were harmful to the mortality and emergence of T. japonicum imagoes, with average LT50 values of 84 minutes and 46 minutes, respectively. Exposure to insecticides caused T. japonicum imagoes to exhibit abnormalities in wing folding and behavioral changes, resulting in reduced activity.